2008
DOI: 10.1007/s11242-008-9296-7
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Counter-Current Imbibition into Core Samples with All Faces Open

Abstract: Counter-current imbibition occurs when brine spontaneously displaces oil from a very strongly water-wet rock. Experiments are usually carried out on cylindrical core plugs which have all of their faces open, mainly because this is easiest to do and also because it appears to give the most reproducible results. The flow patterns are complex, but a reasonable approximation can be obtained by assuming piston-like advance of fronts from the radial outer face and both flat ends. This separates the flow pattern into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…This confirms that, in counter-current imbibition, the relative permeabilities to WP and NWP are not constant values but change with the viscosity ratio of the two fluids. It is the only plausible explanation for the most successful empirical correlation of the effect of viscosity ratio (Mason et al 2010). But just how reliable is the observed difference in k * nw for the two different viscosity oils?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms that, in counter-current imbibition, the relative permeabilities to WP and NWP are not constant values but change with the viscosity ratio of the two fluids. It is the only plausible explanation for the most successful empirical correlation of the effect of viscosity ratio (Mason et al 2010). But just how reliable is the observed difference in k * nw for the two different viscosity oils?…”
Section: Discussionmentioning
confidence: 99%
“…The existence of the CBP was mentioned by Parsons and Chaney (1966), but its effect is usually omitted in analyses of the imbibition process. The CBP is determined by the largest pores at the surfaces where oil is produced as droplets (Li et al 2006;Mason et al 2009;Unsal et al 2009). It may be that small inhomogeneities at the rock surface have a significant effect on the CBP.…”
Section: Introductionmentioning
confidence: 99%
“…14). The most commonly used boundary condition in imbibition experiments is AFO, because it does not need to seal any surface of the core (Babadagli, 2002;Baldwin and Spinler, 2002;Mason et al, 2009;Rostami Ravari et al, 2011). However, the fluid flow patterns under AFO boundary conditions are complex even for homogeneous porous media, which results in that it is very difficult to simulate process of fluid flow by mathematical models.…”
Section: Completely Counter-current Imbibitionmentioning
confidence: 99%
“…In the past few years, various mathematical models have been established for spontaneous imbibition with different boundary conditions by assuming piston-like displacement. The mathematical model for AFO imbibition was established by separating the flow pattern into linear imbibition and radial imbibition by Mason et al (2009b). Mason et al (2012) developed a model for imbibition outwards from a hemispherical depression and reported that oil production was linear with the imbibition time.…”
Section: Introductionmentioning
confidence: 99%